(untitled) (Revista Sistemas de Producción Agroecológicos, 2013)
This work was performed at the level of greenhouse and field at the Universidad de los Llanos, Barcelona seat in Villavicencio municipality, Meta department, with a north latitude of 4° 3 ’and 63° 38’ west longitude, the climate is a tropical rainforest relative humidity of 75% and an average annual rainfall 2500 mm, with bimodal distribution. The overall objective of this study was to determine some biological characteristics, physiological and herbicide response of the plant Hyptis capitata Jacq into Meta department. Prick tests were conducted, seed dormancy, seed viability, emergency depth, morphology and biology. Tests were also conducted mineralogical and chemical composition analysis. Furthermore, tests were used effects of herbicides in pre-emergence and post-emergence. Further tests were conducted this plant as a host of natural enemies, in a design of randomized complete block with 4 replicates, was used as a companion crop and measured the presence of natural enemies and parasitoids on the incidence of some pests of rice. Germination of the species at the surface is greater or up to two inches deep. Persistence ability of this species lies in its latency, or in the germination percentage is very low and that, but in the ability to produce a high amount of seeds (more than 3000 seeds per plant). Furthermore, within the high amount of insect species arriving Hyptis plants, which are present in greater quantity in the Hemiptera, Coleoptera, Hymenoptera orders and Arachnid class, which have a high number of benefits among their representatives Reduviideae, Calcideae, Pompilideae, among others. Also, if using tools of chemical to control Hyptis capitata Jaqc within the pre-emerging the top performer is the oxadiazon and butachlor. The best post-emergent herbicide for control of friar false cord are Azimsulfuron + Metsulfuronmetil, Byspiribae Sodium and Metsulfuronmetil. Finally, the population of Trichogramma spp, and flies Telenomus, Tachinid family was greater in the distribution of H. capitata on the edges and cross.